Employer impact on COVID-19 vaccine uptake among nursing and social care employees in Austria - Ruf, Ann-Kathrin; Völkl-Kernstock, Sabine; Eitenberger, Magdalena; Gabriel, Marcus; Klager, Elisabeth; Kletecka-Pulker, Maria; Klomfar, Sophie; Teufel, Anna; Wochele-Thoma, Thomas (Frontiers in Public Health, 2022)
Introduction Since becoming available, vaccines against COVID-19 have been a focus of public debate. This is particularly relevant among healthcare and social workers, who interact with vulnerable patients and clients on a daily basis. With employers implementing educational programs and offering incentives to raise vaccine willingness among their staff, it is crucial to understand drivers of vaccine acceptance and hesitancy as well as the impact employers can play on vaccine decision-making. Methods We conducted a cross-sectional study via computer-assisted telephone and web interviews. We recruited from a pool of employees from nursing and social care institutions in Vienna and Lower Austria operated by one healthcare NGO. Variables included in the analysis were socio-demographic attributes, reasons for or against the vaccine, sources of information, opinions of mandatory vaccination, and whether respondents had previously been infected with COVID-19 or knew someone who had. Results 86.2% of respondents had received at least one dose of the COVID-19 vaccine. 13.8% were unvaccinated. Vaccinated respondents' main reason for getting the vaccine was to protect themselves (79.6%) as well as others (74.1%), while non-vaccinated respondents cited a fear of short or long-term side effects (58.8 and 42.4%, respectively) as their primary reason for not getting vaccinated. 72.8% of the unvaccinated said no incentive would make them change their mind, while 17.4% specified abstract concepts or systemic change as effective incentives. Monetary incentives were not seen as a motivator. Unvaccinated respondents were significantly more worried about the future than vaccinated respondents (78.8 vs. 26.3%, p < 0.001). They were also significantly more likely to view their employers' vaccine recommendations as “manipulative” (50.6 vs. 12.4%, p < 0.001), while vaccinated respondents were significantly more likely to view them as “supportive” (68.0 vs. 25.9%, p < 0.001). Conclusion While employers have the means to mediate public health decision-making by providing information, deciding to become vaccinated is a more complex process including public debate, world views, political influences, and the uptake of information. Employers can act as mediators for public health decision-making, moving policy measures beyond an individualized view of health choices and health literacy toward more structural, systemic, and community-based efforts.